Decarbonisation through digitalisation: Proposals for transforming the energy sector - Jens Strüker; Martin Weibelzahl; Marc-Fabian Körner; Axel Kießling; Ariette Franke-Sluijk; Mike Herrmann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2021)
The successful and rapid achievement of sustainability and climate protection goals is becoming an ever-greater focus of political, economic, and societal action. Against this background, the energy industry contributes and will further contribute to decarbonisation in Germany and throughout Europe. Indeed, it already provides a significant contribution to the Paris Agreement and European Green Deal. In this light, the next transformation phase to a sustainable energy system is inevitably linked to the modernisation and especially to the digitalisation of the energy industry. The aim of this thesis paper is to intensify the discussion on the digitalisation of the energy industry and, in particular, to outline recommendations for flexible and proactive action by all stakeholders. The University of Bayreuth, the Fraunhofer FIT Project Group Business & Information Systems Engineering and the European transmission system operator TenneT are united by the vision of climate-neutral economic growth based on the innovative strength of the European economy. In 2021, decarbonisation is already shaping the digitalisation of the energy industry. Following on from the steps initiated in recent years to move the energy industry towards greater sustainability in the course of the energy transition, the main concern now is to accelerate sustainable growth while continuing to keep the energy supply secure and economical. A crucial building block in this development is the electrification of additional sectors. Accordingly, we discuss the role of grid expansion with respect to sector coupling and emphasise the digitalisation of end-to-end energy industry processes. In this context, we see decentralised digital identities as a promising way of bridging the current digital gap and addressing the need for digital certificates for thorough decarbonisation. In view of the urgency of climate policy action, we recommend an appropriate innovation policy to enable promising solutions to be tested in an agile way and findings to be drawn rapidly. Finally, we offer an overview of the monitoring of carbon emissions in grid expansion projects. This paper is aimed at political decision-makers, energy industry stakeholders, and all citizens interested in energy policy.
urn:nbn:de:bvb:703-epub-5762-8
Keywords: 650; Digitalization; decarbonization; energy industry; CO2